2016
DOI: 10.3389/fnins.2016.00072
|View full text |Cite
|
Sign up to set email alerts
|

Murine Depression Model and its Potential Applications for Discovering Foods and Farm Products with Antidepressant-Like Effects

Abstract: Advanced societies face increased health problems related to various stresses. Chronic psychological stress is a major risk factor for psychiatric disorders such as depression. Although therapeutic agents reduce several symptoms of depression, most have side effects in a broad range of the population. Furthermore, some victims of depression do not show significant improvement with any drugs, so alternative approaches are needed. Good dietary habits may potentially reduce depressive symptoms, but there is littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Moreover, the locomotor activity of the sCSDS mice was even more inhibited by the presence of social target. This behavioral phenotype under novel environments (conspecies and object) will be a useful indicator in identifying foods and farm products that attenuate social stress-induced deficits …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the locomotor activity of the sCSDS mice was even more inhibited by the presence of social target. This behavioral phenotype under novel environments (conspecies and object) will be a useful indicator in identifying foods and farm products that attenuate social stress-induced deficits …”
Section: Discussionmentioning
confidence: 99%
“…Because sCSDS mice fed MF diet were less vulnerable to stress than those fed AIN-93G, it may be useful to evaluate antistress supplements using AIN-93G diet-fed sCSDS mice. Further studies of nutritional supplementation using this type of mice are needed …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that feed purity influences stress resilience in mice (Goto et al . ,b); therefore, we believe that rodent models provide relevant information relating to feeding management under stressful conditions. Moreover, zoo animals are exposed to various stresses, and abnormal behaviors such as pacing are frequently observed (Koyama et al .…”
Section: Perspectives For the Application Of Rodent Models To Animal mentioning
confidence: 99%
“…Therefore, a paradigm that consists of acute social defeat stress and an evaluation of nest quality will be a convenient tool for screening functional foods and reagents that could potentially contribute to the prevention and treatment of depression. Furthermore, in the future, automatic analysis systems for the evaluation of nest quality should be developed for efficient screening (Okayama et al 2015;Goto et al 2016b).…”
Section: Discovery Of Foods and Nutrients For The Prevention Of Deprementioning
confidence: 99%